Efeitos comportamentais e neuromorfológicos do estresse precoce : uma análise teórico-prática em modelos murinos e humanos - Milanesi, Bruna Bueno (2023)
Early Life Stress is capable of altering behavior, cognition and causing anatomical and histological changes in the nervous system of laboratory animals and humans. This work is divided into two studies, whose objectives were: 1- Produce a descriptive review on the morphofunctional changes produced by ELS in murine and human models; 2- Evaluate the long-term effects (>60 days) of exposure to stressful events in early life, analyzing behavioral and neuromorphological parameters in mice. The first study of this dissertation resulted in the production of a scientific article of descriptive review on the effects of ELS on the central nervous system of rodents and humans, which brings a compilation of data regarding the main encephalic alterations at the structural and cellular level. Regarding the second study of this dissertation, which refers to the experimental part, 24 animals were used, control group (N=12) and stressed group (N=12) equally divided into both sexes. Stress was induced through a combined model of early stress (LBSM), which consists of joining the limited bedding (LB) protocol concomitantly with maternal separation (SM) for 3 hours/day, from postnatal day 2 to 15 After 60 days of life, the animals were analyzed. The following tests were performed to assess depressive/anxious behaviors: 1-Sucrose preference test; 2-Open field; 3-Labyrinth in elevated cross; 4-Light/Dark and 5-Forced Swim. Subsequently, the animals were euthanized and their brains submitted to Nissl's histological technique, associated with Cavalieri's stereological methods for volumetric analysis and planar morphometry of cortical thickness and pyramidal layers of hippocampal CA1 and CA3, and estimation of neuronal and glial densities and relationship glia/neurons in different brain regions. Image analysis was performed using Image Pro Plus software and statistical analysis (unpaired t test) using GraphPad Prism software (p< 0.05). In the elevated plus maze test, ELS females increased their time spent in the open arms (p=0.011) and in the center (p=0.019), reduced their time in the closed arms (p=0.005) and increased their number of entries into the open (p=0.028) and closed (p=0.048) arms. No other behavioral parameters were significantly affected by ELS in males or females. Regarding the cerebral morphometry of males, we observed: (1) ELS increased hippocampal volume between Bregmas 1.46 to Bregmas 2.06 (p=0.011), with a significant increase occurring in the most rostral portion of the hippocampus, between Bregma 1.46 to Bregma 1.70 (p=0.001); (2) ELS increased cerebral cortical thickness (p=0.000006) and hippocampal CA1 pyramidal layer thickness (p=0.018); and (3) ELS reduced cortical neuronal density in the infralimbic area of the medial prefrontal cortex (p=0.016). Analyzing the data related to the cerebral morphometry of the females, it is observed: (1) ELS caused an increase in the thickness of the pyramidal layer of the hippocampal CA1 (p=0.00006); (2) ELS reduced cortical neuronal density in the prelimbic (p=0.048) and infralimbic (0.017) areas; (3) ELS reduced neuronal density in the basolateral amygdala (p=0.041) and glial density in the cingulate cortex (p=0.025). The behavioral changes found are restricted to changes in the elevated plus maze test in females. In turn, the ELS protocol affected brain anatomy and histology differently in males and females. Our results suggest that long-term behavioral responses to ELS, in mice, related to depression and anxiety, may be more significant in females and that brain morphometric changes found in males submitted to ELS may not translate into behavioral changes analyzed by the tests performed in this dissertation, but perhaps they are related to deficits in other higher functions.